Investigating EFL Students Self-Efficacy on the Use of QuillBot Paraphrasing Tool in Academic Writing - Andriani, Agis; Fatimah, Asri Siti; Permatasari, Sylvia Arini (Institut Agama Islam Negeri (IAIN) Curup, 2024)
The present study aimed to investigate the self-efficacy of EFL students regarding their use of the QuillBot paraphrasing tool in academic writing. A qualitative research method was employed, and data were gathered through interviews. The participants consisted of four EFL students who were currently in the process of writing their theses and utilizing the QuillBot paraphrasing tool. Data analysis was conducted using NVIVO thematic analysis.The findings indicated that EFL students' self-efficacy in utilizing the QuillBot paraphrasing tool was not satisfactory. This lack of self-efficacy was influenced by various factors, including behavioral, social, and personal aspects. Among these factors, behavioral elements had the most significant impact as they directly affected the students' competence in academic writing. The participants' belief in their own academic writing abilities was undermined by behavioral factors, as they experienced difficulties in vocabulary and grammar usage. Furthermore, the study revealed that the social environment played a crucial role in enhancing EFL students' self-efficacy. Specifically, the support and encouragement received from lecturers and classmates positively influenced the participants' self-belief and confidence in utilizing the QuillBot paraphrasing tool. In conclusion, this research suggests that EFL students' self-efficacy in using the QuillBot paraphrasing tool for academic writing can be improved by addressing behavioral challenges and fostering a supportive social environment.